Towards a more inclusive agricultural insurance program - Celia M. Reyes; Aubrey D. Tabuga; Nicoli Arthur B. Borromeo; Arkin A. Arboneda; Carlos C. Cabaero (Philippine Institute for Development Studies (PIDS), 2019)
Typhoons, pests and other natural calamities cause the country, particularly the agricultural sector, significant damages. For instance, Typhoons Yolanda (Haiyan) and Ompong (Mangkhut) have caused PHP 35 billion and PHP 27 billion worth of agricultural damages, respectively, based on estimates by the Department of Agriculture. Given that a third of the country's workforce depend on the agriculture sector, it is crucial that efforts are undertaken towards mitigation of the effects of these shocks and risks. One of these efforts is agricultural insurance as provided for by the Philippine Crop Insurance Corporation (PCIC). Using information from the PCIC, key informant interviews and focus group discussions with agricultural producers, and findings from earlier studies on agricultural insurance, this study examines the constraints in, opportunities, and efforts for achieving impact and inclusion of agricultural insurance programs in the Philippines.
Keywords: 330; Philippine Crop Insurance Corporation; agricultural insurance; Registry System in Basic Sectors in Agriculture